Multi-beam modulated metasurface antenna for 5G backhaul applications at K-band - Ruiz-García, Jorge; Faenzi, Marco; Mahmoud, Adham; Ettorre, Mauro; Potier, Patrick; Pouliguen, Philippe; Sauleau, Ronan; González-Ovejero, David (Comptes Rendus. Physique, 2021)
We explore the use of a new modulated metasurface (MTS) antenna topology as solution for wireless backhaul at K band. The proposed structure is composed of a quasi-optical beamformer, which feeds the modulated MTS radiating aperture. These two elements are vertically stacked in a two-layer pillbox architecture to produce a very compact antenna. Furthermore, our design is able to provide several beams at different pointing angles and, hence, it offers the possibility of discrete beam steering by beam switching. The employment of a modulated MTS and the compactness given by the pillbox approach lead to a high-gain and low-profile antenna that could be an appealing solution for mobile backhaul networks.